2006
DOI: 10.1677/joe.1.06991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the hypothalamic–pituitary–adrenal axis susceptibility upon single-dose i.m. depot versus long-acting i.v. triamcinolone acetonide therapy: a direct pharmacokinetic correlation

Abstract: The effects of single injections of glucocorticoid (GC) depot suspension and of long-acting GC were studied in conscious dogs. Both the depot suspension GC triamcinolone-16,17-aacetonide (TAA) and the long-acting triamcinolone acetonide-21-dihydrogen phosphate (TAA-DHP) decreased basal and ACTH-stimulated cortisol levels and in a specific timedependent way. Before treatment, all dogs had normal basal and peak cortisol responses to ACTH challenge (13-15 and O120 nmol/l at 1 h respectively). Intravenous TAA-DHP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
(30 reference statements)
0
8
0
1
Order By: Relevance
“…Screening should therefore be timed, if possible, at least 1 week after the exogenous glucocorticoid has been tapered to a physiological dose or removed. 13 Prolonged released formulations (intra-articular and epidural, especially triamcinolone), cause low level cortisol and a blunted response to ACTH stimulation for 4-6 weeks, outside of CYP3A4 inhibition 41,42 and likely for longer with it. Test results need to be interpreted with caution and with endocrinology input.…”
Section: Investigation Of Ics/sai and Management Of Highrisk Co-prescmentioning
confidence: 99%
“…Screening should therefore be timed, if possible, at least 1 week after the exogenous glucocorticoid has been tapered to a physiological dose or removed. 13 Prolonged released formulations (intra-articular and epidural, especially triamcinolone), cause low level cortisol and a blunted response to ACTH stimulation for 4-6 weeks, outside of CYP3A4 inhibition 41,42 and likely for longer with it. Test results need to be interpreted with caution and with endocrinology input.…”
Section: Investigation Of Ics/sai and Management Of Highrisk Co-prescmentioning
confidence: 99%
“…; Abraham et al . ; Bentz ). Parenteral triamcinolone acetonide has been used in the past for treatment of systemic diseases such as RAO (Lapointe et al .…”
Section: Commonly Used Glucorticoidsmentioning
confidence: 99%
“…It was hypothesized that particulate steroid preparations may provide a local depot effect with constant release of the active drug from the administration site over a longer time period compared to non-particulate steroids [53].…”
Section: Efficacy Of Various Steroids In Lumbar Epidural Injectionsmentioning
confidence: 99%
“…The duration of action of intramuscular administered triamcinolone acetonide representing a particulate glucocorticoid was studied in an investigation with dogs and compared to intravenous administered triamcinolone acetonide dihydrogen phosphate (TAA-DHP), which represents the non-particulate steroid [53]. It was shown that a single dose of the particulate glucocorticoid (triamcinolone acetonide) after intramuscular administration revealed a much longer duration of action of up to 4 weeks on the hypothalamicpituitary-adrenal axis activity in dogs than a similar intravenous dose of its analogue, the non-particulate steroid (TAA-DHP) [53].…”
Section: Efficacy Of Various Steroids In Lumbar Epidural Injectionsmentioning
confidence: 99%
See 1 more Smart Citation